Analisis Kinerja Guru Profesional dalam Penerapan Pembelajaran Daring di SD - Ratna Budiastri; Erif Ahdhianto; Suhartono Suhartono; Ratna Budiastri; Erif Ahdhianto (Universitas Negeri Malang, 2021)
Abstract: The purpose of this research was to obtain information about professional teachers' performance in the application of online learning regarding 3 aspects: planning, implementation, and evaluation. This research used a descriptive quantitative research approach. The sample in this research was 56 professional teachers, in State Elementary Schools throughout Pagelaran District, Malang Regency. The data analysis technique used descriptive statistical analysis. The results of this research indicate that: (1) online learning planning obtained a percentage of 78.96 percent belonging to the medium category; (2) the implementation of online learning obtained a percentage of 81.46 percent belonging to the high category; (3) evaluation of online learning obtained a percentage of 79.13 percent belonging to the medium category. The overall results obtained a percentage of 80.06 percent which indicated that the performance of professional teachers in the application of online learning in State Elementary Schools throughout the Pagelaran District of Malang Regency is in the medium categories. Abstrak: Tujuan dari penelitian ini adalah untuk memperoleh informasi kinerja guru profesional dalam penerapan pembelajaran daring mengenai 3 aspek yakni: merencanakan pembelajaran, melaksanakan pembelajaran, dan mengevaluasi pembelajaran. Penelitian ini menggunakan pendekatan kuantitatif deskriptif. Sampel pada penelitian ini sebanyak 56 guru profesional, di SD Negeri Se-Kecamatan Pagelaran Kabupaten Malang. Hasil penelitian menunjukkan bahwa: (1) merencanakan pembelajaran daring diperoleh persentase sebesar 78,96 persen tergolong kategori sedang; (2) melaksanakan pembelajaran daring diperoleh persentase sebesar 81,46 persen tergolong kategori tinggi; (3) mengevaluasi pembelajaran daring diperoleh persentase sebesar 79,13 persen tergolong kategori sedang. Hasil keseluruhan diperoleh persentase sebesar 80,06 persen yang menunjukkan kinerja guru profesional dalam penerapan pembelajaran daring di SD Negeri Se-Kecamatan Pagelaran Kabupaten Malang tergolong kategori sedang.